Hedonic test of tree leaf herbal tea using various statistical approaches - Wangiyana, I Gde Adi Suryawan; Triandini, I Gusti Agung Ayu Hari (UNIVERSITAS MUHAMMADIYAH MATARAM, 2022)
This research compares the hedonic assay of several tree-plant herbal teas with different statistical approaches. Leaves of cacao, muntingia, guava, avocado, and moringa were processed into the raw material of herbal tea. Herbal tea beverage made by boiling raw material at 80°C for 5 minutes with 5% w/v sweetener. Thirty panelists aged of 18 – 33 years old were given a response on the hedonic test. There were five scales of the hedonic test: like extremely (5), like slightly (4), neither like nor dislike (3), dislike slightly (2), and dislike extremely (1). Hedonic test results were analyzed using Kruskal-Wallis, Friedman, ANOVA-CRD, ANOVA-RBD, LSD, error standard, and spider web. The numeric score of the hedonic test from panelists based on color and taste parameters has shown correlated results among Kruskal-Wallis, Freidman, and ANOVA methods. However, the Friedman method has different analysis results from other statistical methods on the numeric score of the aroma parameter. LSD, error standard, and spider web have shown that cacao tea has the best color and taste parameter score among other herbal tea. It could be concluded that cacao tea is the best tree-plant herbal tea based on a hedonic test analyzed by several statistical methods.